(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Suicidal deaths are very frequently encountered by forensic experts in day-to-day practice. Here, we shed light on an unusual complicated suicide case, with features of hanging, head trauma and traumatic asphyxia. Allegedly, a dead body of a 65 years old man was found stuck in a shaft between the elevator and a wall, in a multistorey building, with ligature material placed around his neck. The ligature material was torn in two parts and the other part was found tied over the railing upstairs, in proximity to the elevator shaft, in front of his room. Suicide notes were found with the body. During the autopsy, two loops of faint ligature marks were present on the neck and on further exploration, extravasation of blood was present over the strap muscles of neck and carotid sheath. Upper part of the body was congested and there was a clear line of demarcation. Head injury was also present with skull fractures and cerebral haemorrhages. Signs of asphyxia were seen on the internal organs. This case, illustrating a peculiar pattern of injuries is reported for future reference of pathologists to help in identifying and anticipating such injuries in similar cases of suicide.